Learning curve. NT open learning: clinical supervision -- part 8: implementation problems. - Lucas S; Jones A (Nursing Times)
This week in NT Open Learning, Sharon Lucas, lecturer in nursing at City University, London, and Alun Jones, lecturer, School of Nursing, Midwifery and Health Visiting, University of Manchester, with additional material by Deborah Glover, clinical editor, Nursing Times, consider issues related to the implementation of clinical supervision. In order to avoid problems, it is useful to do some groundwork before introducing clinical supervision and to plan its introduction in a systematic way